Factors of Forced Early Marriage Reviewed from Islamic Law in Indonesia (Case Study of Air Hitam Village, Gebang District, Langkat Regency) - Saputra, Jeffry; Iwan, Iwan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the factors of coercion in early marriage. find out how Islamic law in Indonesia analyzes the coercion of underage children into marriage. This research was designed using qualitative methods to be able to explain in as much detail as possible about forced early marriage. This research is normative-empirical research with a sociological approach. The primary data source was obtained from interviews with several respondents, while the secondary data source was obtained from several references that explain forced marriage in Indonesian Islamic law. Meanwhile, the analysis technique is descriptive. The results of this research found that many factors led to attempts to force early marriage in Air Hitam village due to several factors such as economic reasons, low education, and lack of understanding of religion. So, from the results of this research, it is concluded that forced early marriage is caused by economic factors, education, and religious understanding. analysis of Islamic law regarding forced marriage of underage children, referring to the majority of ulama or the majority of ulama saying that it is haram or not permissible to force girls (underage) to marry. The majority of ulama view that forcing the marriage of minor girls (underage) does not bring benefits at all, it even becomes a shackle for the child's freedom so that his future is threatened.